2005
DOI: 10.1111/j.1469-8137.2005.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf nitrogen and phosphorus stoichiometry across 753 terrestrial plant species in China

Abstract: Summary• Leaf nitrogen and phosphorus stoichiometry of Chinese terrestrial plants was studied based on a national data set including 753 species across the country.• Geometric means were calculated for functional groups based on life form, phylogeny and photosynthetic pathway, as well as for all 753 species. The relationships between leaf N and P stoichiometric traits and latitude (and temperature) were analysed.• The geometric means of leaf N, P, and N : P ratio for the 753 species were 18.6 and 1.21 mg g − 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

105
633
63
24

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 832 publications
(825 citation statements)
references
References 27 publications
105
633
63
24
Order By: Relevance
“…Although the growth rate of the Masson pine in PF3 decreased, its large biomass and different sources of nitrogen and phosphorus could cause phosphorus to become a limiting factor for the Masson pine growth. The growth of the Masson pine was mostly limited by the availability of phosphorus in our study areas, which was concordant with the law of P deficiency in the low-latitude region (Hedin 2004;Han et al 2005;Zhang et al 2005).…”
Section: N-p Stichometry and Nutrient Limitation In Leaves And Soilsupporting
confidence: 61%
“…Although the growth rate of the Masson pine in PF3 decreased, its large biomass and different sources of nitrogen and phosphorus could cause phosphorus to become a limiting factor for the Masson pine growth. The growth of the Masson pine was mostly limited by the availability of phosphorus in our study areas, which was concordant with the law of P deficiency in the low-latitude region (Hedin 2004;Han et al 2005;Zhang et al 2005).…”
Section: N-p Stichometry and Nutrient Limitation In Leaves And Soilsupporting
confidence: 61%
“…This observation is not surprising because the uptake, transport, and allocation mechanisms for P and N are very similar in plants (Feild & Brodribb, 2001; Jeschke, Kirkby, Peuke, Pate, & Hartung, 1997; Kilgore, Patel, Sharma, Maya, & Kielhorn, 2014; Lynch, 1995; Mimura, 1995; Niklas et al., 2005; Schachtman, Reid, & Ayling, 1998). However, our results also show that seedling P content scales isometrically with N content across the four species, whereas prior studies report that a ⅔ scaling exponent for P versus N across large plants (Han, Fang, Guo, & Zhang, 2005; Niklas, 2006; Niklas et al., 2005; Reich et al., 2010; Wright et al., 2004). This difference may be partly due to the gradual decrease in physiologically active biomass (and the N contained therein) as plants continue to grow in size (Ågren, 2008; Niklas & Enquist, 2002; Peng et al., 2010).…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have demonstrated that N, P and the N:P of leaves noticeably change with temperature, precipitation and soil condition along latitudinal gradients (Han et al 2005;Reich and Oleksyn 2004). In contrast, Reich et al (2010) reported a consistent allometric scaling pattern of N L to P L with a uniform 2/3 log-log slope across dramatic biogeographical gradients.…”
Section: Introductionmentioning
confidence: 90%
“…It has been found that the scaling of N concentration as a function of P concentration in different plant organs can be well described by allometric relationship, in which the common log-log slope was significantly smaller than 1 (Ågren 2008;Elser et al 2010;Kerkhoff et al 2006;Reich et al 2010;Wright et al 2004). Many studies have demonstrated that the allometric relationship between leaf N (N L ) and leaf P (P L ) are similar at various scales, spanning from the local to global scale, with ranges of 0.67 to 0.72 for slopes (a) of the scaling functions (Garten 1976;Han et al 2005;Kerkhoff et al 2006;Reich et al 2010;Wright et al 2004). Furthermore, allometric relationship have also been detected in the roots and stems, for which the slopes (a) of the scaling functions are 0.76 (Yuan et al 2011) and 0.70 (Kerkhoff et al 2006), respectively.…”
Section: Introductionmentioning
confidence: 99%